2022
DOI: 10.1002/ese3.1220
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and emission characteristics investigation of a marine diesel engine powered by diesel/biodiesel/n‐butanol blends 

Abstract: In this paper, a three‐dimensional simulation model of the engine cylinder is established using commercial simulation software AVL‐Fire, and the accuracy of the model is verified with experimental results. The effects of diesel/biodiesel/n‐butanol blends on diesel engine performance, and combustion and emissions characteristics were investigated by performing simulation operations on the model. The combustion process in the cylinder was simulated for 0%, 5%, 10%, 15%, and 20% of n‐butanol in the fuel mixture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…According to Yu et al [22], as the N-butanol ratio increased within a fuel mixture, soot and CO emissions decreased. Nalla et al [23] used Prunus domestica seeds as fuel and n-butanol as an additive and found that the cylinder combustion had higher efficiency and lower fuel usage on account of the presence of n-butanol.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yu et al [22], as the N-butanol ratio increased within a fuel mixture, soot and CO emissions decreased. Nalla et al [23] used Prunus domestica seeds as fuel and n-butanol as an additive and found that the cylinder combustion had higher efficiency and lower fuel usage on account of the presence of n-butanol.…”
Section: Introductionmentioning
confidence: 99%
“…This study addresses these limitations and conducts a comprehensive comparison of CO 2 , CO, NO, and soot emissions from marine LPG, gasoline, and diesel engines. This analysis is based on the AVL FIRE simulation program, which is a reliable tool validated in various studies [20][21][22][23][24]. The modeling of the simulated LPG engine, that is, the reference engine model in this study, is conducted based on the information of the marine LPG engine, which is the first candidate for type approval for small ships in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…However, the engine's braking capacity was decreased, the brake ratio's fuel consumption rose, and NO x emissions rose. 23 The use of mathematical models to forecast the brake-specific fuel consumption and exhaust emissions of a diesel engine in terms of variables such as load and volume percentages of Fe 3 O 4 magnetic nanoparticles. 24 Using ANN, the influence of a ternary blend of diesel (80%), ethanol (10%), and n -butanol (10%) on the combustion and emission parameters were examined.…”
Section: Introductionmentioning
confidence: 99%